2016
DOI: 10.1080/19443994.2015.1051588
|View full text |Cite
|
Sign up to set email alerts
|

Removal of acetaminophen from the contaminated water using adsorption onto carbon activated with NH4Cl

Abstract: A B S T R A C TThe efficacy of NH 4 Cl-induced activated carbon (NAC) in removing acetaminophen (ACT) as a model of non-steroidal anti-inflammatory pharmaceutical compounds in aqueous solution is investigated in this study. The experiments were performed in different conditions of solution pH, contact time, initial concentration, adsorbent concentration, and solution temperature to the adsorption of ACT on NAC. The results showed that ACT adsorption onto adsorbent was not pH-dependent in the range of 2-9; but,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 37 publications
(54 reference statements)
0
14
0
2
Order By: Relevance
“…Adsorption on activated carbon is a well-established technology for water treatment owning to its versatility and high efficiency, including for PhCs (Putra et al, 2009;Calisto et al, 2015;Mashayekh-Salehi and Moussavi, 2016). Nevertheless, it is an expensive adsorbent, US $20-22/kg (Babel and Kurniawan, 2003), which limits its widespread applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption on activated carbon is a well-established technology for water treatment owning to its versatility and high efficiency, including for PhCs (Putra et al, 2009;Calisto et al, 2015;Mashayekh-Salehi and Moussavi, 2016). Nevertheless, it is an expensive adsorbent, US $20-22/kg (Babel and Kurniawan, 2003), which limits its widespread applicability.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Although paracetamol, used as fever reduction drug and for pain relief, is relatively safe at lower doses, it has various hazards, such as gastrointestinal disease, liver failure, hepatotoxic potential, and centrilobular necrosis in the liver. 9,10 100 E M İ R E et al…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, adsorption with activated carbon is an available removal method for the removal of organic and inorganic pollutants due to its cost‐effective, large surface area, numerous microporous structure, good surface chemistry, and renewability. Up to now, many adsorption studies have mainly focused on the removal of liquid contaminants, such as acetaminophen, dye, and heavy metal . However, studies on the adsorption of gaseous CH 3 COOH on activated carbon have hardly been reported.…”
Section: Introductionmentioning
confidence: 99%